Butterflies As Eco-tour Attractions In Lebih Tourist Resort, Gianyar, Bali - Dalem, Anak Agung Gde Raka (Metamorfosa: Journal of Biological Sciences, 2021)
Research on butterflies as ecotour attractions in Lebih tourist resort, Gianyar was conducted in 2019. Objectives of this research was to find out species of butterflies that was found in that resort as well as to find out its potentials ecotour attractions.  Samples of butterflies were collected through exploration of research sites, while other data were collected through interview. Butterflies sampled on site were diidentified and then  recorded.  Butterflies potentials as ecotour attractions were analized based on tourists’s perception.  The location where butterflies have been used as ecotour attractions, as well as how to set up a package butterfly based ecotour would be reported.   This research showed that there were 30 species of butterflies that have been identified in Lebih tourist resort. Based on observation and interview conducted it could be concluded that there has been butterfly based ecotourism as well as butterfly based ecotourism have been available on the research site.  In addition, Lebih tourist resort has had a potential to develop butterly based ecotourism.  This can can be  indicated by the diversity of butterlies on the site, ie. 30 species, that can be used as ecotour attractions.  The potential can be supported by the existence of other attractions including  cultural attractions and man made attractions.  From the perspective of accessibility, Lebih tourist resort was relatively easy to access, especially by using on line transport facilities.  The existence of tourist facilities in Lebih tourist resort has increased.  Support for the development of Lebih tourist resort has been provided by the government. After appointment of nine villages as well as some other adjacent villages as a tourist resort, the local government as well as other parties has built tourist facilities as well as hosted tourism events in this resort.   Keywords — Bali, butterfly, ecotourism potential, ecotourism, Lebih tourist resort